PEDAGOGICAL ANALYSIS OF MUSIC CULTURE AND ART IN THE DAYS OF AMIR TEMUR AND TEMURIDS. HISTORICAL ROOTS OF THE CULTURE AND ART OF THE PRIMITIVE PERIOD OF UZBEKISTAN - Mirkomilova Nigora (Journal of new century innovations, 2023)
This article outlines the historical roots of the culture and art of the primitive period of Uzbekistan.